The Effect of Profitability and Dividend Policy on Firm Value : (A Case Study on Manufacturing Companies Listed in the Jakarta Islamic Index for the Period 2019–2024) - Erwin, Erwin; Zuliansyah , A.; Pratomo, Dimas (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the effect of profitability and dividend policy on firm value among manufacturing companies listed on the Jakarta Islamic Index (JII) during the 2019–2024 period. Firm value in this research is measured using the Price-to-Book Value (PBV) ratio as an indicator of investor perceptions of the company’s prospects. Methods: A quantitative approach is employed, utilizing multiple linear regression analysis with secondary data derived from the annual financial reports of six manufacturing companies selected through purposive sampling. Results: The results of this study are expected to provide empirical evidence on the role of profitability and dividend policy in influencing firm value, supporting signaling theory and stakeholder theory in the context of investment decision-making. This research also offers practical implications for company management in formulating appropriate financial strategies to enhance firm value and investor appeal. Keywords: Profitability, Dividend Policy, Firm Value, Jakarta Islamic Index, Manufacturing Companies